(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2012)
Exposure to aflatoxins (AFs) in the diet may favour the development of hepatocellular carcinoma (HCC) and the acute exacerbation of hepatitis in chronic hepatitis B virus (HBV) carriers. Measurement of biomarkers such as aflatoxin M1 (AFM1), a metabolite of aflatoxin B1 (AFB1), in urine allows for the assessment of populations exposed to aflatoxins. The aim of this study was to investigate the occurrence of aflatoxin M1 in the urine of HBV carrier and non-carrier patients. One group included 43 randomly selected HBV carriers treated at two hospitals in the city of Maringa, Brazil, from March to June 2008. Control group consisted of 29 healthy adult volunteers with anti-HBs positive and HBsAg negative test results. Detection of AFM1 was performed by fluorescence using high performance liquid chromatography (HPLC) and post-column derivation with the Kobra Cell®. Of the 72 samples analysed, 05/29 (17.2%) AFM1 positive samples were from HBV non-carriers, and 16/43 (37.2%) of samples were from chronic HBV carriers. This study showed AFM1 in the urine of the two surveyed population. However, there is evidence that the chronic HBV carriers have a higher risk of developing HCC due to additive interaction between AFs and HBV.